Velocity and acceleration-based differential plyometric training effects on young basketball players - Arede, J.; Sevin, I.; Williams, M.; Mikolajec, K.; Aguiar, R. A. B.; Schöllhorn, W. (Journal of Human Kinetics, 2025)
This study aimed to examine the impact of velocity and acceleration-based differential plyometric jump training on physical performance of youth basketball players. Twenty-six trained youth male players (14.5 ± 1.7 years; U14 [n = 14], U16 [n = 5], and U18 [n = 7]) were grouped into experimental and control groups. The experimental group completed two sessions per week of velocity-based differential plyometric training for 14 weeks (3 sets x 5 jumps with 20-s intervals of passive recovery between jumps and 2-min breaks between sets). Before each repetition, participants received verbal instruction to perform a different fluctuation. The control group continued regular training. Bilateral and unilateral countermovement jump (CMJ) height, the 20-m sprint test, and the Modified 505 Agility (M505) test were evaluated before and after the intervention. The training program yielded statistically significant improvements in the experimental group's CMJ bilateral jump height. Additionally, moderate improvements in the CMJR (Countermovement Jump Right Leg) and M505R (Modified 505 Agility Right) tests (BF10 > 3 to 10) were observed after the training program (d ranged from 0.66 to 1.12). The control group demonstrated moderate improvements in the M505R (Modified 505 Agility Right) and M505L (Modified 505 Agility Left) tests (BF10 > 3 to 10) (d = 0.65). Models combining different variables provided the best fit for the data in different physical variables. The results indicate that velocity and acceleration-based differential plyometric training can be a suitable strategy for improving physical performance of youth basketball players.